India’s medical tourism gets Africans’ attention - Pavithra Rao (Africa Renewal, 2017)
Nagged by a sharp back pain three years ago, Abidemi Ogbonna from Lagos, Nigeria, decided to visit a nearby hospital called Apollo. Thinking it was just a minor problem, she was shocked when her physician informed her that she urgently needed a kidney transplant.